Multicamera Real-Time 3D Modeling for Telepresence and Remote Collaboration - Benjamin Petit; Jean-Denis Lesage; Clément Menier; Jérémie Allard; Jean-Sébastien Franco; Bruno Raffin; Edmond Boyer; François Faure (International Journal of Digital Multimedia Broadcasting)
We present a multicamera real-time 3D modeling system that aims at enabling new immersive and interactive environments. This system, called Grimage, allows to retrieve in real-time a 3D mesh of the observed scene as well as the associated textures. This information enables a strong visual presence of the user into virtual worlds. The 3D shape information is also used to compute collisions and reaction forces with virtual objects, enforcing the mechanical presence of the user in the virtual world. The innovation is a fully integrated system with both immersive and interactive capabilities. It embeds a parallel version of the EPVH modeling algorithm inside a distributed vision pipeline. It also adopts the hierarchical component approach of the FlowVR middleware to enforce software modularity and enable distributed executions. Results show high refresh rates and low latencies obtained by taking advantage of the I/O and computing resources of PC clusters. The applications we have developed demonstrate the quality of the visual and mechanical presence with a single platform and with a dual platform that allows telecollaboration.